Design and Performance Evaluation of Network-assisted Control Strategies for HTTP Adaptive Streaming - Giuseppe Cofano; Luca De Cicco; Thomas Zinner; Anh Nguyen-Ngoc; Phuoc Tran-Gia; Saverio Mascolo (ACM Trans. Multimedia Comput. Commun. Appl. (Special issue best papers of ACM MMSys 2016), 2017)
This article investigates several network-assisted streaming approaches that rely on active cooperation between video streaming applications and the network. We build a Video Control Plane that enforces Video Quality Fairness among concurrent video flows generated by heterogeneous client devices. For this purpose, a max-min fairness optimization problem is solved at runtime. We compare two approaches to actuate the optimal solution in an Software Defined Networking network: The first one allocates network bandwidth slices to video flows, and the second one guides video players in the video bitrate selection. We assess performance through several QoE-related metrics, such as Video Quality Fairness, video quality, and switching frequency. The impact of client-side adaptation algorithms is also investigated.
Keywords: quality of experience; network-assistance; fairness; control plane; dash; adaptive video streaming